دراسة المحتوى الفيتو كيميائي والبنية التشريحية لمختلف ‏وضعيات وعمر اوراق النخيل - قويدري سعيدة; باسي وئام (University of Eloued جامعة الوادي, 2025)
As part of this study, a comprehensive examination was conducted on palm fronds collected from the vicinity of Hamma Lakhdar University in El Oued. Samples were taken from both the northern and southern orientations, as well as from fronds at different developmental stages (young and mature). Additionally, samples were collected from three distinct anatomical regions of the frond: the base, middle, and tip. The research focused on detailed structural aspects, alongside the analysis of secondary metabolites of biochemical importance, such as phenolics and flavonoids. The microscopic analysis included measurements of various fine morphological parameters, such as stomatal density, thickness of different tissue layers (palisade, spongy, and epidermis), dimensions of epidermal and parenchymal cells, and elements of vascular bundles such as the number of fibers, area and diameter of the vascular cylinder, stomatal pore diameter, and guard cell width, all assessed from both the upper and lower surfaces of the leaf. To determine the moisture content, samples were weighed before and after natural drying, allowing for precise calculation of water content. The leaves were then processed in the laboratory by grinding and extraction to determine the concentrations of phenolic and flavonoid compounds, given their association with plant defense functions and biological activity. The results revealed clear variations in structural characteristics and chemical content depending on the frond's location, geographical orientation, and age. These findings indicate the palm tree's ability to undergo structural and physiological adaptation in response to varying environmental conditions, highlighting its scientific and practical significance.
فيزيولوجيا النبات
Keywords: Anatomical and chemical study – Different positions and ages of palm frond leaves.; عمر أوراق سعف النخيل